Community pharmacists' involvement in smoking cessation: familiarity and implementation of the National smoking cessation guideline in Finland - Sandström Patrick; Pietilä Kirsi; Linden Kari; Kurko Terhi; Airaksinen Marja (BMC, 2010)
Abstract Background Guidelines on smoking cessation (SC) emphasize healthcare cooperation and community pharmacists' involvement. This study explored the familiarity and implementation of the National SC Guideline in Finnish community pharmacies, factors relating to Guideline familiarity, implementation and provision of SC services. Methods A nationwide mail survey was sent to a systematic, sample of community pharmacy owners and staff pharmacists (total n = 2291). Response rate was 54% (n = 1190). Factors related to the SC Guideline familiarity were assessed by bivariate and multivariate analysis. Results Almost half (47%) of the respondents (n = 1190) were familiar with the SC Guideline and familiarity enhanced Guideline implementation. The familiarity was associated with the respondents' perceptions of their personal SC skills and knowledge (OR 3.8); of customers' value of counseling on nicotine replacement therapy (NRT) (OR 3.3); and regular use of a pocket card supporting SC counseling (OR 3.0). Pharmacists' workplaces' characteristics, such as size and geographical location were not associated with familiarity. In addition to recommending NRT, the pharmacists familiar with the Guideline used more frequently other Guideline-based SC methods, such as recommended non-pharmacological SC aids, compared to unfamiliar respondents. Conclusions SC Guideline familiarity and implementation is crucial for community pharmacists' involvement in SC actions in addition to selling NRT products. Pharmacists can constitute a potential public health resource in SC easily accessible throughout the country.